Response of irrigated wheat cultivars to different nitrogen rates and sources - Teixeira Filho,Marcelo Carvalho Minhoto (2009)
High wheat yields require good N fertilization management. The objective of this study was to evaluate the effects of different N applications at sowing using Entec (N source with nitrification inhibitor) and urea (traditional N source) at covering, on four wheat cultivars. The experiment was conducted in a randomized block design in a factorial scheme, with four replications, at the Experimental Station of the Faculdade de Engenharia de Ilha Solteira - UNESP, on a dystrophic, epi-eutrophic alic Red Latosol with loamy texture, formerly under savannah vegetation. Four N rates (0, 60, 120, and 180 kg ha-1) were tested, applied at sowing in the case of Entec and top-dressed 40 days after plant emergence in the case of urea, and the four wheat cultivars E 21, E 22, E 42, and IAC 370. The yield of the wheat cultivars E 21 and E 42 was highest. Plant height and lodging index of cultivar E 22 were greatest, with consequently lowest grain yield. There was no significant difference between Entec (applied at sowing) and urea (top-dressed) in terms of grain yield and yield components. Nevertheless, urea resulted in a higher N leaf content, and Entec in a larger number of undeveloped spikelets. High nitrogen rates influenced the hectoliter mass negatively, affecting wheat grain quality. Grain yield increased under N rates of up to 82 kg ha-1 N, through Entec applied at sowing or top-dressed urea.